Grain development and yield in maize subjected to defoliation levels - Rezende, Wender Santos; Brito, Césio Humberto de; Brandão, Afonso Maria; Franco, Cláudio José Faria; Ferreira, Maurício Viana; Ferreira, Adão de Siqueira (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the influence of defoliation of maize on grain development and yield. Six trials were conducted in different growing seasons and locations and at two yield levels. A randomized complete block design was used, with seven replicates. Defoliation was made at the V4 vegetative stage of maize (four expanded leaves), and treatments consisted of: removal of the two basal leaves, removal of the four expanded leaves, total removal of leaves (aerial plant section), and a control (without defoliation). The following were evaluated: length of the vegetative period; and, at pre‑harvest, plant height, ear insertion height, plant lodging percentage, stalk‑breaking strength, force required to pull the plant, and yield. The removal of four leaves and the total removal of leaves increased the length of the vegetative period and reduced plant height, ear insertion height, and stalk strength against breaking. These defoliation levels also reduced yield, mainly with the total removal of leaves. The force required to pull the plant was not influenced by defoliation. Removal of four leaves and of all leaves reduces grain yield, respectively, in 6.25 to 14,05 in the evaluated hybrids.
Keywords: Zea mays; leaf area; leaf integrity; vegetative period; yield potential